Recurrent Aortic Coarctation with Aneurysmatic Thinning of the Subaortic Basal Ventricular Septum in a Young Man - Bingöl, Gülsüm Bulut; Özden, Özge; Tokdil, Hasan; Tokdil, Kardelen Ohtaroğlu; Ökçün, Barış (Cerrahpaşa Medical Journal, 2024)
Cite this article as: Bulut Bingöl G, Özden Ö, Tokdil H, Ohtaroğlu Tokdil K, Ökçün B. Recurrent aortic coarctation with aneurysmatic thinning of the subaortic basal ventricular septum in a young man. Cerrahpaşa Med J. 2024;48(1):98-100.